If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -2x + 2 = 5x Reorder the terms: 8 + 2 + -2x = 5x Combine like terms: 8 + 2 = 10 10 + -2x = 5x Solving 10 + -2x = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 10 + -2x + -5x = 5x + -5x Combine like terms: -2x + -5x = -7x 10 + -7x = 5x + -5x Combine like terms: 5x + -5x = 0 10 + -7x = 0 Add '-10' to each side of the equation. 10 + -10 + -7x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -7x = 0 + -10 -7x = 0 + -10 Combine like terms: 0 + -10 = -10 -7x = -10 Divide each side by '-7'. x = 1.428571429 Simplifying x = 1.428571429
| -4(n-3)= | | 7(x+35)=273 | | 13/15+(8/15)= | | 8.28=5r | | -2(6+x)= | | 2(x+12)=3*x-31 | | (10j-7)-(9j+2)= | | 3x+22+5y+11=180 | | 5y+11=180 | | x-2+3=7 | | (63+5)+(72-3)= | | 8+5(x+3)+7x=x | | (7y+1)(3y-4v-2)= | | 2(4x+1)=42 | | 9+3m= | | (7t+5)+(8t-3)= | | 4x^3-3x^2+9=0 | | 4x-8=79+9x | | 2x+2u=5 | | 1/2(6x-10)+1/3(6+9x)= | | 4x^2-19x+23=-4x+9 | | 12v-11v=18 | | 10(2.1q-2)+(7.5q+19)= | | 5x-2x-2x=17 | | 9m+m+3m-12m+3m=12 | | 8g-6g-8=2g | | 12z-11z=8 | | 5x+(3x-2)=-3-(-4x) | | x=(x*0.1)+(x*0.02)+5+100 | | (13x+50)-(80x+120)= | | 8k-7k=5 | | (13x+50)+(80x+120)= |